Patience as a virtue: Religious and psychological perspectives - Schnitker, Sarah A. (Research in the social scientific study of religion, 2007)
For millennia, theologians, moral philosophers, and writers have identified patience as an important aspect of virtue and excellence of character. This study seeks to understand the religious and psychological underpinnings of patience and presents the Patience Scale to measure individual differences in the trait. Undergraduate psychology students (n = 324) completed survey packets containing items to measure patience as well as the Values in Action Strengths Scale (VIA-IS), measures of religiousness/spirituality, and measures of self-control, time perspective, the Big Five, and mindfulness. The 24 strengths of the VIA-IS were related in varying degrees to patience, but sufficient independence from existing strengths was demonstrated. Patience was significantly related to spiritual transcendence and to religious behaviors. Anticipated uses of the Patience Scale and implications for future research are discussed.